2014
DOI: 10.1007/s00497-014-0250-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cytological and transcriptomic analysis of pollen development in autotetraploid and diploid rice

Abstract: Autotetraploid rice has greater genetic variation and higher vigor than diploid rice, but low pollen fertility is one of the major reasons for low yield of autotetraploid rice. Very little is known about the molecular mechanisms of low pollen fertility of autotetraploid rice. In this study, cytological observations and microarray analysis were used to assess the genetic variation during pollen development in autotetraploid and diploid rice. Many abnormal chromosome behaviors, such as mutivalents, lagged chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
166
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(185 citation statements)
references
References 32 publications
13
166
0
1
Order By: Relevance
“…Similar to normal diploid rice and consistent with descriptions presented in Wu et al, 2014, meiosis in the PMCs of the diploid rice hybrid could be divided into the following nine developmental stages: prophase I, consisting of leptotene, zygotene ( Fig. 2A), pachytene (Fig.…”
Section: Meiosis In Diploid and Autotetraploid Hybridssupporting
confidence: 85%
See 3 more Smart Citations
“…Similar to normal diploid rice and consistent with descriptions presented in Wu et al, 2014, meiosis in the PMCs of the diploid rice hybrid could be divided into the following nine developmental stages: prophase I, consisting of leptotene, zygotene ( Fig. 2A), pachytene (Fig.…”
Section: Meiosis In Diploid and Autotetraploid Hybridssupporting
confidence: 85%
“…We previously showed that 125 genes were down-regulated during PMC meiosis in autotetraploid rice (E1-4x) versus diploid rice (E1-2x) and identified one prominent functional gene class with five genes associated with DNAdependent DNA replication (GO: 0006261) in the biological process category. However, we did not identify any significant GO terms in the cellular component category (Wu et al, 2014). In our study, we identified 231 genes that were down-regulated in PMC meiosis of autotetraploid rice (E245-4x) relative to the diploid line (E245-2x) during PMC meiosis (Fig.…”
Section: Genes Differentially Down-regulated In Autotetraploid Rice Wmentioning
confidence: 72%
See 2 more Smart Citations
“…These changes may trigger complicated interactions between the repair of DNA damage and the regulation of cell cycles. Another aspect of genome shock maybe also include parentage-biased patterns of gene expression and the abnormal upand down-regulation of offspring genes and abnormality in the very nascent hybrid genomes: e.g., 2nF 1 and 2nF 2 (59,60). We hypothesize that the alteration of expression of these genes drives polyploidization.…”
Section: Discussionmentioning
confidence: 97%